2016
DOI: 10.1007/s00345-016-1765-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary kidney injury molecule-1 levels in renal stone patients

Abstract: In renal stone patients, the elevated urine KIM-1/Cr ratio levels increase further according to stone size. KIM-1/Cr ratio is a promising marker might be helpful in monitoring the damage created by stone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…Dede et al [28] stated in their study that post-RIRS second hour KIM-1/Cr ratio was high; yet, KIM-1/Cr levels returned to preoperative levels 24 h after surgery. Balasar et al [30] found that urine KIM-1/Cr ratios of kidney stone patients who underwent PNL and RIRS increased to the postoperative 4th h and decreased below the preoperative value on the 14th day. They stated in their study that with the increase of stone load, KIM-1/Cr levels elevated as well.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Dede et al [28] stated in their study that post-RIRS second hour KIM-1/Cr ratio was high; yet, KIM-1/Cr levels returned to preoperative levels 24 h after surgery. Balasar et al [30] found that urine KIM-1/Cr ratios of kidney stone patients who underwent PNL and RIRS increased to the postoperative 4th h and decreased below the preoperative value on the 14th day. They stated in their study that with the increase of stone load, KIM-1/Cr levels elevated as well.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Under normal conditions, KIM-1 is absent in the urine; however, it is increased after the development of the following conditions: acute renal failure (caused by ischemia or nephrotoxicity), urolithiasis (particularly in patients who underwent surgical treatment), and cystic kidney disease [ 8 , 31 , 32 ]. Kidney injury molecule-1 expression was found to be significantly associated with glomerular disease and interstitial damage [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…measured preoperative and postoperative urine KIM-1/Cr levels in patients with micro PNL, RIRS, and PNL. A signi cant decrease was detected in postoperative KIM-1/Cr levels in RIRS and PNL grougroupspared to micro PNL at the end of the study (p = 0.010, p = 0.001 respectively) (20). In another study, KIM-1/Cr and NGAL/Cr levels were detected two hours after the operation at a statistically signi cantly increased level compared to preoperative levels (p = 0.04, p = 0.02 respectively Preoperative KIM-1/Cr levels show the homogeneous distribution of the groups.…”
Section: Discussionmentioning
confidence: 86%